Exploring consensus for the optimal sealant use to prevent air leak following lung surgery: a modified Delphi survey from The European Society of Thoracic Surgeons. (2nd December 2020) - Brunelli, Alessandro; Bölükbas, Servet; Falcoz, Pierre Emmanuel; Hansen, Henrik; Jimenez, Marcelo F.; Lardinois, Didier; Scarci, Marco; Viti, Andrea; Walker, Ian; Warren, Tim
Abstract: : OBJECTIVES: The use of sealants is one of the methods available to reduce the occurrence of intraoperative air leaks. The objective of this modified Delphi survey among ESTS members is to understand the attitudes of clinicians to the optimal use of sealants in air leak management. METHODS: To understand the attitudes of a wider sample of clinicians, a questionnaire was developed highlighting key issues through 37 statements. Respondents were invited to score their level of agreement with each. A modified Delphi methodology was used to review responses with a threshold of agreement for consensus of 75%. RESULTS: A total of 258 responses were received (response rate 17%). Respondents agreed that prolonged air leaks are a common complication in thoracic surgery presenting a burden to the patient and increasing the costs of care. There is clear support for the use of sealants to reduce costs and improve the efficiency of healthcare provision and duration of chest tube use in selected high-risk patients with intraoperative air leak at the end of the lung surgery. Respondents also agreed that, due to often complex nature of thoracic surgery, sealants should be developed specifically for this application. CONCLUSION: There is a clear role for sealants in the management of air leaks and certain surgical procedures demand their use (i.e. lung volume reduction surgery, decortication). This opinion-based consensus review helps to raise the debate about the burden of air leaks in thoracic surgery in order that this issue is recognized in practice and informs the optimal use of sealants in lung surgery.